2011
DOI: 10.1111/j.1471-0366.2010.00294.x
|View full text |Cite
|
Sign up to set email alerts
|

Agrarian Change under Globalization: Markets and Insecurity in Turkish Agriculture

Abstract: This paper argues that deepening commodification in Turkish agriculture has changed the lives of farmers in significant ways. Global circuits have swept away the accustomed networks of information, production and marketing which had been largely established and maintained by comprehensive governmental support policies. New institutions have come into the picture establishing the links between small producers and larger markets. With state policy strengthening the domination of the market, prices and demand pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
66
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(70 citation statements)
references
References 39 publications
0
66
0
1
Order By: Relevance
“…6 See Köymen (2008Köymen ( ),Önal (2010 and Gürel (2011) for the critiques of Keyder's(1987) thesis. The main argument in these studies is that the average peasant incomes in Turkey were still low and do not have a positive impact on urban inequality.…”
Section: The Bargaining Aspectmentioning
confidence: 99%
See 1 more Smart Citation
“…6 See Köymen (2008Köymen ( ),Önal (2010 and Gürel (2011) for the critiques of Keyder's(1987) thesis. The main argument in these studies is that the average peasant incomes in Turkey were still low and do not have a positive impact on urban inequality.…”
Section: The Bargaining Aspectmentioning
confidence: 99%
“…It is mentioned in a few paragraphs in empirical studies examining the relationship between land and income inequality, in studies whose focus is not on the link between land and urban distribution (Griffin, Khan and Ickowitz, 2002) and in case studies (De Janvry, 1981;Harris, 1978;Keyder, 1987, Amsden, 19891990) of selected regions. Building on these earlier insights, this study offers a thorough theoretical analysis by developing a model based on the Harris-Todaro (1970) framework as extended by Fields (1975Fields ( , 2005.…”
Section: Introductionmentioning
confidence: 99%
“…The monoculture structure of these large-scale production systems is at the root of many economic problems for farmers throughout the world (Altieri & Rosset, 1996). The situation is not different in Turkey; Keyder and Yenal (2011) report that deregulation efforts left small farmers vulnerable to the fluctuations of world markets on inputs and outputs. This, coupled with the commodification of land and labor, led small farmers to seek employment outside farming.…”
Section: Introductionmentioning
confidence: 99%
“…Long-term organic comparison trials in the US have shown that organic practices have the potential to better store carbon and nitrogen, resulting in higher soil quality, and allowing farmers to remain competitive in the marketplace (Delate et al, 2015). These characteristics of organic agriculture provide a solution for the economic problems of farmers by reducing unemployment and the dependence on off-farm inputs and help farmers to capture a higher proportion of the value added by giving a specific position to their products (Keyder & Yenal, 2011;Aktar & Ananias, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, any evaluation of the AKP's balance sheet will reveal the following: (i) public administration has been radically transformed by successive "reforms" (Oğuz 2008); (ii) a massive privatisation programme has been implemented and the revenue generated by privatisation was unprecedented when compared to the previous phases of neo-liberalism (Öniş 2011); (iii) a series of independent and autonomous regulatory boards for strategic sectors were established and exempted from the direct surveillance and inspection of the central government and the parliament; (iv) amendments to the Labour Act allowed increased subcontracting, increased flexibility and decreased unionisation (Özdemir andYücesan-Özdemir 2006, Çelik 2015); (iv) policies related to agriculture have resulted in the contraction of that sector, with Turkey drifting away from agricultural self-sufficiency (Aydın 2010;Keyder and Yenal 2011). This last change has generated a surplus population in rural areas which has begun flowing to urban centres, and enlarged the urban reserve army of labour.…”
Section: Turkey Takes the Neo-liberal Roadmentioning
confidence: 99%